A Survey on Congestion in Wireless Multimedia Sensor Networks - Mamadapur, Panchaxari; Shiva Prasad, KH (International Journal of Computer Sciences and Engineering, 2025)
Wireless Multimedia Sensor Networks (WMSNs) have emerged and shifted the focus from the typical scalar wireless sensor networks to networks with multimedia devices that are capable to retrieve video, audio, images, as well as scalar sensor data. WMSNs are able to deliver multimedia content due to the availability of inexpensive CMOS cameras and microphones coupled with the significant progress in distributed signal processing and multimedia source coding techniques. In this paper, we outline the congestion, types of congestion, congestion control. As congestion has a significant impact on Quality of Services (QoS).